Comparative study of soils of different landforms under rubber with special reference to erodibility indices/factor - Satisha, G.C.; Ulaganathan, A. (Journal of Plantation Crops, 2009)
Soil erodibility factor ‘K’ is a quantitative description of the inherent erodibility of a particular soil and it represents the susceptibility of soil particles to detachment and transport by both rainfall and runoff. Soils of different landforms under rubber (Hevea brasiliensis) in Kerala were studied with special reference to erodibility factor. Soils of nineteen-soil series developed on different landforms representing 70 per cent of the total potential rubber growing area were selected and the susceptibility of these soils to erosion was assessed by soil ratios and erodibility factor ‘K’ using soil survey information. The soil erodibility factor ‘K’ varies from 0.273 to 0.473, 0.353 to 481, 0.299 to 0.459 and 0.287 to 0.468 for soils developed on charnockite, laterite, khondalite and granite-gneiss landform, respectively. The soils of Vazhoor and Vijayapuram series developed on charnockite, Kaipuzha and Anayadi series of laterite, Kadambanad series of khondalite and soils of Pallippadi series identified in the granite-gneiss landform contained relatively high values of clay ratio and silt/clay ratio indicating that these soils are more susceptible to erosion than the other soils. Among the landforms, soils developed on laterite were relatively more susceptible to erosion compared to soils of other landforms. The study also revealed that soils with higher content of intermediate particle size fractions between sand and clay showed more erodibility risk than the soils with higher clay and higher sand content. In general, all the soils have moderate to high risk of erosion, thus needs suitable soil conservation measures to reduce soil loss and protect existing productivity.